Resistência á fratura e avaliação da microdureza dentinária de coroas dentais submetidas a diferentes protocolos de clareamento intracoronário - Galoza, Marina Oliveira Gonçalves [UNESP] (2014)
The purpose of this study was to evaluate the effect of the hydrogen peroxide and the carmine red pigment (CR) at 3:1 and 1:1 ratio, on the fracture resistance and dentin microhardness of bovine teeth submitted to tooth bleaching. Forty endodontically treated incisors were subjected to bleaching and divided into: G1(WHP3): 35% HP with CR (Whiteness HP) at 3:1 ratio; G2(WHP1) : 35% HP (Whiteness HP) with CR at 1:1 ratio ; G3(OPA): 38% HP (Opalescence Boost) e G4(CT): control group. Three bleaching sessions were performed with an interval of 7 days between them; the bleaching gel was applied to the buccal surface and placed inside the pulp chamber. 7 days after from the last bleaching session, the teeth were submitted to the fracture resistance test at the testing machine. Similar bleaching protocols were used in other identical groups to assess the reduction of dentin microhardness. The microhardness was measured, using knoop microhardness, before and after 4 sessions of bleaching protocols. G2 presented lower fracture resistance than G4 (p <0.05), but similar to G1 and G3 (P> 0.05).The dentin microhardness reduction was similar among the groups. Hydrogen peroxide and pigment at 1:1 ratio caused fracture resistance reduction, when compared to control group, but did not influence on dentin microhardness.